2004
DOI: 10.1002/ana.20030
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor fiber tracking shows distinct corticostriatal circuits in humans

Abstract: A landmark of corticostriatal connectivity in nonhuman primates is that cortical connections are organized into a set of discrete circuits. Each circuit is assumed to perform distinct behavioral functions. In animals, most connectivity studies are performed using invasive tracing methods, which are nonapplicable in humans. To test the proposal that corticostriatal connections are organized as multiple circuits in humans, we used diffusion tensor imaging axonal tracking, a new magnetic resonance technique that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
338
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 514 publications
(393 citation statements)
references
References 35 publications
52
338
1
2
Order By: Relevance
“…S2 and S3) was consistent with the segmentation pattern reported in previous studies (Cohen et al, 2009;Croxson et al, 2005;Lehericy et al, 2004;Voorn et al, 2004), which confirmed the probabilistic tracking process of diffusion tensor images in the present study.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…S2 and S3) was consistent with the segmentation pattern reported in previous studies (Cohen et al, 2009;Croxson et al, 2005;Lehericy et al, 2004;Voorn et al, 2004), which confirmed the probabilistic tracking process of diffusion tensor images in the present study.…”
Section: Resultssupporting
confidence: 92%
“…Anatomically, the striatum widely accepts fiber projections from subcortical and cortical regions such as the amygdala, hippocampus and medial frontal cortex, making up an interconnected neural network (Cohen et al, 2009;Lehericy et al, 2004). Functional studies found that these regions' response to novelty was positively correlated with NS (Krebs et al, 2009).…”
Section: Novelty Seekingmentioning
confidence: 99%
“…In an effort to conciliate both points of view, we propose that the striatum might hold a twofold role in language processing comprising controlled processes of lexical access via the link to executive areas and implicit rule computations via more language specific circuits. This proposal is compatible with recent findings from diffusion tensor imaging (Lehéricy et al, 2004) showing that the human striatum is connected to both the dorsal-lateral prefrontal cortex, known to subserve executive functions (e.g., Stuss & Knight, 2002), and to portions of Broca's area, which is claimed to impact on combinatorial aspects of language processing (e.g., Hagoort, 2005). Likewise, it is compatible with data of implicit manipulation tasks showing that rule use in artificial grammar learning (Lieberman, Chang, Chiao, Bookheimer, & Knowlton, 2004) and in word morphology (Teichmann et al, 2006) are tied to the striatum whereas lexical operations are not (Heindel, Salmon, Shults, Walicke, & Butters, 1989;Salmon, Shimamura, Butters, & Smith, 1988;Shimamura, Salmon, Squire, & Butters, 1987).…”
Section: Discussionsupporting
confidence: 93%
“…al (2005) showed that speed of phonological processing is correlated with tracer binding potential in left putamen (Tettamanti et al, 2005b). A study using diffusion tensor imaging recently showed that the putamen is primarily connected to motor and pre-motor regions as well as posterior regions of the prefrontal cortex (Lehericy et al, 2004). These posterior regions of the frontal cortex have been associated with phonological segmentation and articulatory control (Bitan et al, submitted;Poldrack et al, 1999).…”
Section: Discussionmentioning
confidence: 99%